2013
DOI: 10.1021/cm304098x
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Precise Synthesis of Thiolated Au10–12, Au15, Au18, and Au25 Nanoclusters via pH Controlled CO Reduction

Abstract: Large-scale production of thiolated Au nanoclusters (NCs) of tunable sizes is pivotal to realizing their practical applications. Here, we present a simple one-pot synthesis method for gram-scale production of various discretesized Au NCs (Au 10−12 , Au 15 , Au 18 , and Au 25 ) protected by different thiol ligands. The key design in our method is to use a gaseous reducing agent, carbon monoxide (CO), to support a mild reaction environment for a slow and well-controlled growth of Au NCs. The pH of the reaction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
244
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 253 publications
(266 citation statements)
references
References 51 publications
20
244
2
Order By: Relevance
“…With increasing reaction temperature, however, a gradual absorption decrease at 279 nm is observed, whereas the absorption at 310 nm increases ( Figure S9, Supporting Information). [39][40][41] This indicates that the high temperature facilitates the aggregation and fusion of smaller Au clusters into bigger ones. At the same time it can be seen that the direct absorption peak of CuSe at 432 nm also increases, which implies the deposition of Cu on the clusters at higher temperature by increasing the reactivity of the Cu sources.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…With increasing reaction temperature, however, a gradual absorption decrease at 279 nm is observed, whereas the absorption at 310 nm increases ( Figure S9, Supporting Information). [39][40][41] This indicates that the high temperature facilitates the aggregation and fusion of smaller Au clusters into bigger ones. At the same time it can be seen that the direct absorption peak of CuSe at 432 nm also increases, which implies the deposition of Cu on the clusters at higher temperature by increasing the reactivity of the Cu sources.…”
Section: Resultsmentioning
confidence: 95%
“…Control experiment indicated that Au strongly aggregated in the absence of DT, whereas the CuZnSe 2 domains remained stable, proving the role of DT in stabilizing the Au domains and that of OLA in stabilizing CuZnSe 2 . [39][40][41] Moreover, DT can reduce Au 3+ under moderate heating, thus producing DT-stabilized Au clusters. Although DT is capable to reduce elemental Se in the presence of OLA, as the Au 3+ to Au 0 reduction potential is much higher than that of Se 0 to Se 2− this makes the reduction of Au 3+ by DT more competitive (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Au 15 , Au 18 , Au 25 [92], Au 38 [93] and Au 144 NCs [94] can all be prepared, and some of them have been fully characterized by single crystal X-ray diffraction [95]. These clusters break down the barriers between molecular systems and NP systems and are potential catalysts with unusual properties.…”
Section: Discussionmentioning
confidence: 99%